Changes of Serum Ficolin-3 and C5b-9 in Patients with Heart Failure - Li, Hongli; Zhang, Fangfang; Zhang, Dan; Tian, Xiang (Pakistan Journal of Medical Sciences, 2021)
Objectives: To investigate the correlation of serum ficolin-3 and C5b-9 with cardiac function and NT-proBNP in patients with heart failure. Methods: Sixty patients with heart failure admitted to the Baoding First Central Hospital from May 2019 to May 2020 were selected and divided into three groups according to the classification of New York Heart Association (NYHA). Patients with NYHA grade II, III, and IV were included into group A, B, and C, respectively. Among the population undergoing physical examination at the same time, 20 cases with no significant difference in age and gender from the experimental group were selected as the control group (Group-N), and their clinical data were recorded. The serum levels of ficolin-3, C5b-9 and NT-proBNP in each group were detected and compared. Results: The serum concentrations of ficolin-3 and C5b-9 in Group N were significantly different from those in Group A, B and C (p<0.05), the difference between Group C and Group A and B was statistically significant (p<0.05), there was no significant difference between group A and B (p>0.05). The correlation analysis between serum ficolin-3 and NT-proBNP showed that serum ficolin-3 was negatively correlated with NT-proBNP (r=-0.606, p<0.0001), while the correlation analysis between serum C5b-9 and NT-proBNP showed that serum C5b-9 was positively correlated with NT-proBNP (r=0.499, p<0.0001). According to the etiology of heart failure, patients with heart failure were divided into coronary heart disease (25 cases), dilated cardiomyopathy (15 cases) and others (20 cases). The differences of ficolin-3 and C5b-9 among patients were compared, and there was no statistical difference (p<0.05). Conclusion: Ficolin-3 was inversely associated with the severity of heart failure, while C5b-9 was positively associated with the severity of cardiac impairment. Both of them have nothing to do with the etiology of heart failure. doi: https://doi.org/10.12669/pjms.37.7.4151 How to cite this: Li H, Zhang F, Zhang D, Tian X. Changes of Serum Ficolin-3 and C5b-9 in Patients with Heart Failure. Pak J Med Sci. 2021;37(7):1860-1864. doi: https://doi.org/10.12669/pjms.37.7.4151 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.